2009
DOI: 10.1179/107735209799449680
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and Morbidity among Farmers, Nonfarming Rural Men, and Urban Referents: A Prospective Population-Based Study

Abstract: A cohort of 1,220 farmers, 1,130 nonfarming rural men, and 1,087 urban referents from Sweden were monitored for 12 years. Farmers had lower mortality than urban referents for all causes of death (hazard ratio [HR] = 0.51; 95% confidence interval [CI], 0.37-0.71), cancer (HR = 0.44; 95% CI, 0.24-0.78) and cardiovascular diseases (HR = 0.60; 95% CI, 0.36-0.99). Nonfarming rural men had lower mortality than urban referents for all causes of deaths (HR = 0.81; 95% CI, 0.70-0.94). Farmers and nonfarming rural men h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…We have followed a cohort of rural men over 12 years [22]. In a previous study we found that daily intake of fruit and vegetables in combination with a high dairy fat intake was associated with a lower risk of coronary heart disease [23].…”
Section: Introductionmentioning
confidence: 99%
“…We have followed a cohort of rural men over 12 years [22]. In a previous study we found that daily intake of fruit and vegetables in combination with a high dairy fat intake was associated with a lower risk of coronary heart disease [23].…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have suggested a unique pattern of morbidity and mortality among farmers [2-4]. Farmers have a remarkable deficit in total mortality, cardiovascular diseases, diabetes mellitus, psychiatric disorders and total cancer compared with the other populations, but appear to have higher prevalence rates of musculoskeletal diseases, respiratory diseases, hearing loss, skin disorders, accidental death and cancer of the skin, stomach, brain, and prostate, as well as the nervous, lymphohematopoietic systems [2,3,5,6]. …”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that this population has a greater risk of several cancers (non-Hodgkin's lymphoma, Hodgkin's disease, multiple myeloma, prostate, connective tissue, skin, stomach, and brain) [1], respiratory diseases such as chronic obstructive pulmonary disease [2,3], musculoskeletal pain [4,5], reproductive outcomes [6] and accidents [7]. Some others also reported higher risk for neurologic diseases such as Parkinson’s disease [8,9] or cognitive decline and dementia [10-12].…”
Section: Introductionmentioning
confidence: 99%
“…Some others also reported higher risk for neurologic diseases such as Parkinson’s disease [8,9] or cognitive decline and dementia [10-12]. On the other hand, some findings also suggested that this population would less often suffer from other conditions, such as cardiovascular diseases [1,5,6], some types of cancer (lung, colon, oesophagus and bladder [1][5]) or asthma (particularly for farm exposure in the childhood [13,14]). In terms of mortality, the literature suggests quite consistent results, showing a lower mortality for all causes of death, and particularly lower mortality by cancer [1,5]; only few studies suggested the reverse such as in Australia [15].…”
Section: Introductionmentioning
confidence: 99%